Interaction among Stakeholder Representatives and Their Stakes in Participatory Forest Resources Management - Sunthornhao, Pasuta (วารสารวนศาสตร์ไทย, 2022)
A study on the selection of stakeholder representatives for participatory forest resource management (PFRM) and their stake interaction was carried out during 2007 in the Huai Dau watershed (HDW) in Roi Et province, northeast Thailand. The HDW represented a land-use system unit, which combined agricultural and forestry activities. The research objectives were to determine and identify the major stakeholders (MaSTs) in PFRM who were in charge of stakeholder representation. The methodology began with a consideration of the biophysical, socio-economic and institutional situation. Data gathering and analysis were carried out in order to classify households and categorize stakeholders employing a partial process of participatory landscape lifescape appraisal (PLLA). Stakeholder analysis was based on the determination and identification of MaSTs who were the decision makers in PFRM based on four criteria: number of stakes (NS), duration of stakeholding (DS), degree of dependency (DD) and degree of accountability (DA). Moreover, the final analysis of interaction between stakeholders and stakes ranked the stakes based on the frequency of whole stakes. The study found eight MaSTs from the twelve stakeholders; two were individual stakeholders (ISTs), from a resident business (RB) and resident farm (RFa), while the other six were organization/institutional stakeholders (OSTs), being government organizations - forestry office (GOs-FO), government organizations - school (GOs-S), local government units - subdistrict administrative organization (LGUs-SAO), local government units - subdistrict leading office (LGUs-SLO), local government units - village leading office (LGUs-VLO) and people organizations - arts and craft center (POs-AC). The GOs-S was a highly effective MaST because this stakeholder achieved the highest total weighted mean score (TWMS). In addition, water was the most common stake followed by abundant soil, amenity, fuelwood and non wood forest products (NWFPs). Keywords: participatory forest resources management, stakeholder analysis, major stakeholder, decision maker, participatory landscape lifescape appraisal